PEMBERIAN DIET SERAT TINGGI DAN PENGARUHNYA TERHADAP PENURUNAN KADAR KOLESTEROL DARAH PADA PASIEN PENYAKIT JANTUNG KORONER DI RUANG RAWAT INAP PENYAKIT DALAM RSUP Dr. MOHAMMAD HOESIN PALEMBANG TAHUN 2008 - Eduan Effendi; Yuli Hartati; Arief Dwi Setyo Haripamilu (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The position of heart disease as the cause of death in Indonesia has increased. Diseases of heart and blood vessels has become the number one cause of death in Indonesia. Data Household Health Survey (SKRT) MOH in 1992 is to mortality and morbidity of heart disease by 15.4 percent..In 1995 the patient's blood vessel disease increased to 18.9 percent and in 2001 reached 24.4 percent and until now ranked first. This research is a quantitative research design, experimental Pre namely research, without control, by using the research design before and after. The average levels of fiber before giving a high fiber diet is 32.3920 grams with a standard deviation of 1.27878 grams. After providing a high fiber diet gained an average level of 46.0073 grams of fiber is the standard deviation of 5.07560.The mean difference between before and after the provision of a high fiber diet is 13.6153 with standard deviation 5.14905. The results of statistical tests obtained p value = 0.000. The average cholesterol levels before giving a high-fiber diet is 243.6667 mg / dl with a standard deviation of 10.92398 mg / dl. After providing high-fiber diet gained an average cholesterol level was 188.8282 mg / dl with a standard deviation of 5.41998 mg / dl. The mean difference between before and after the provision of a high fiber diet is 54.8383 mg / dl with a standard deviation of 10.82645 mg / dl. The results of statistical tests obtained p value = 0.000. The average HDL level before giving a high-fiber diet is 35.0667 mg / dl with a standard deviation of 4.05933 mg / dl. After giving a high-fiber diet gained an average HDL level was 65.3033 mg / dl with a standard deviation of 10.16795 mg / dl. The value of the mean difference between before and after giving a high fiber diet is -30.2367 mg / dl with a standard deviation 8.03653 mg / dl. The results of statistical tests obtained p value = 0.000. The average levels of LDL before giving high-fiber diet is 153.0333 mg / dl with a standard deviation of 16.75479 mg / dl. After giving high-fiber diet gained an average LDL was 94.9763 mg / dl with a standard deviation of 24.21840 mg / dl. The mean difference between before and after the provision of a high fiber diet is 58.0570 mg / dl with a standard deviation of 22.54031 mg / dl. The results of statistical tests obtained p value = 0.000.